2003
DOI: 10.1523/jneurosci.23-37-11621.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human Cerebral Activation during Steady-State Visual-Evoked Responses

Abstract: Flicker stimuli of variable frequency (2-90 Hz) elicit a steady-state visual-evoked response (SSVER) in the electroencephalogram (EEG) with the same frequency as the stimulus. In humans, the amplitude of this response peaks at approximately 15 Hz, decreasing at higher stimulation frequencies. It was not known whether this peak response corresponds to increased synaptic activity in the visual cortex or to other mechanisms [for instance, the temporal coherence (phase summation) of evoked responses]. We studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
210
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(237 citation statements)
references
References 34 publications
18
210
1
1
Order By: Relevance
“…An artificial scotoma was created by placing a small flickering square achromatic target (1.12 by 1.12°) on the background in the lower left visual field at 9.43°eccentricity (8°across, 5°down) flickering between black (luminance 2.5 cd/m 2 ) and white (luminance 98.4 cd/m 2 ) at a rate of 7.5 Hz (eight screen-refresh cycles). This frequency was chosen because it produces the largest amplitude oscillatory MEG signal (38). The lower half of the visual field was chosen for placement of the target, because filling-in has been shown to be more robust (9) and because MEG signals have been shown to be stronger for stimuli presented in the lower visual field (39).…”
Section: Methodsmentioning
confidence: 99%
“…An artificial scotoma was created by placing a small flickering square achromatic target (1.12 by 1.12°) on the background in the lower left visual field at 9.43°eccentricity (8°across, 5°down) flickering between black (luminance 2.5 cd/m 2 ) and white (luminance 98.4 cd/m 2 ) at a rate of 7.5 Hz (eight screen-refresh cycles). This frequency was chosen because it produces the largest amplitude oscillatory MEG signal (38). The lower half of the visual field was chosen for placement of the target, because filling-in has been shown to be more robust (9) and because MEG signals have been shown to be stronger for stimuli presented in the lower visual field (39).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects participated in several runs comparing combinations of 6, 10, 12, 15, 20, and 30 Hz with both overlapping and nonoverlapping stimuli. These frequencies were chosen to match reports of successful experiments in the SSVEP literature (e.g., Regan, 1989;Cheng et al, 2002 2 ;Beverina et al, 2003;Gao et al, 2003;Pastor et al, 2003) within the limited set of frequencies available a monitor with a 60 Hz refresh rate. Although there were substantial differences between subjects, SSVEP differences were most apparent with checkerboxes at 6 and 15 Hz and lineboxes at 10 and 12 Hz.…”
Section: Pilot Testingmentioning
confidence: 99%
“…It is worth to comment that for both SSVEP response and classification studies, only O1, O2 and O3 electrodes were selected after the application of a Common Average Reference (CAR) spatial filter, which is based on studies that suggest that the highest values of energy for SSVEP detection are located on the occipital area of the cortex (Di Russo et al, 2007;Krolak-Salmon et al, 2003;Pastor et al, 2003;Sammer et al, 2005;Zhang et al, 2006). Thus, the twelve aforementioned electrodes were used at the initial stage only for application of the CAR spatial filter.…”
Section: Eeg Recordingmentioning
confidence: 99%
“…These frequencies were chosen due to: 1) our previous studies (Tello et al, 2014a;2014b;2014c) have shown that these generate strongest SSVEP responses; 2) safety recommendations specified in Fisher et al (2005); 3) studies conducted by Pastor et al (2003) about the relationship between visual stimuli and SSVEP-evoked amplitudes recommend these frequencies; 4) studies conducted by Herrmann (2001) showing peaks of SSVEPs at ∼15 Hz.…”
Section: Stimulation Unit (Su)mentioning
confidence: 99%